Perempuan Migran dan Pelacur Terselubung (Kajian Tentang Faktor Penarik Terjadinya Prostittusi Terselubung di Kabupaten Wajo, Sulawesi Selatan) - Musdaliah Mustadjabar; Ashari Ismail (Seminar Nasional LP2M UNM, 2019)
The rise of the practice of prostitution carried out by migrant women in Wajo — raises the problem - anomalies of disharmony and the weakening of social and cultural moral order. The practice of prostitution, which is carried out by migrant women, is understood as a complex social problem. Prostitution as a social pathology, is - hypermodern, which is caused by various factors (including push factors) such as: the condition of women themselves, the drive to fulfill economic needs, sexual desire, weak social order (including omission by unscrupulous village officials) — a number of factors this includes, — the source of anomic problems, - in the constellation, the creation of a social order that is as hard as, far from the norm perspective, in the social structure of the Bugis Makassar culture in Wajo.